Portrayal of tobacco smoking in popular women's magazines: a content analysis - Kasujee, Naseera; Britton, John; Cranwell, Jo; Lyons, Ailsa; Bains, Manpreet (Oxford University Press, 2016)
Background: Whilst many countries have introduced legislation prohibiting tobacco advertising and sponsorship, references to tobacco continue to appear in the media. This study quantified and characterized tobacco smoking content in popular women's magazines.